2020
DOI: 10.1177/1468087420960870
|View full text |Cite
|
Sign up to set email alerts
|

Performance improvement of turbocharged SI engine by post-oxidation enhancement in exhaust gas in-homogeneity

Abstract: In this research, the improvement of mixing and pulsation in exhaust manifold with a design and implementation of bypass adapter at exhaust port were deeply investigated. This in-turn can improve the post-oxidation phenomena and hence emissions and engine performance could be enhanced. This research investigation includes 1-D, 3-D simulations and experimental validation on a 4-cylinder turbocharged spark ignition (SI) engine. Firstly, the 1-D and 3-D simulation models were developed and calibrated with the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…This had appeared due to the higher in-homogeneity in secondary combustion that leads to unstable post-oxidation in the exhaust manifold. This can be improved if the mixing of unburned gas species with scavenged O2 will be able to enhanced in the exhaust manifold [7]. The…”
Section: Gas Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…This had appeared due to the higher in-homogeneity in secondary combustion that leads to unstable post-oxidation in the exhaust manifold. This can be improved if the mixing of unburned gas species with scavenged O2 will be able to enhanced in the exhaust manifold [7]. The…”
Section: Gas Temperaturementioning
confidence: 99%
“…At the same time, less unburned fuel is brought into the catalyst, which prevents the catalyst from rising in temperature. In past, another methodology for the post-oxidation has been also adopted such as, secondary air injection in exhaust port that can enable secondary reaction (post-oxidation) and could increase enthalpy at turbocharger upstream and hence turbo-lag can be reduced [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the inhomogeneity plays a significant drawback at the higher overlap which restricts the efficient postoxidation. 4,5,9,10 Several kinds of simulative and experimental research have been conducted on the scavenging (VVT tuning) based post-oxidation phenomena. [1][2][3][4][5][6][7]9,11,12 Guenther et al performed a simulative study on the scavenging-based post-oxidation phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…4,5,9,10 Several kinds of simulative and experimental research have been conducted on the scavenging (VVT tuning) based post-oxidation phenomena. [1][2][3][4][5][6][7]9,11,12 Guenther et al performed a simulative study on the scavenging-based post-oxidation phenomena. The reaction kinetics mechanism including CO and H 2 was investigated and found that the H 2 shows the key element for the fast reaction.…”
Section: Introductionmentioning
confidence: 99%